2012
DOI: 10.1177/1359105312440300
|View full text |Cite
|
Sign up to set email alerts
|

Illustrated medication instructions as a strategy to improve medication management among Latinos: A qualitative analysis

Abstract: Although illustrated medication instructions may improve medication management among vulnerable populations, little prior research has evaluated their use among Latinos. We conducted focus groups and interviews with Latino patients with diabetes at two safety net clinics in Tennessee to understand medication taking practices and perceptions of illustrated medication instructions. Patients reported confidence in being able to take medications, but demonstrated a lack of understanding of medication instructions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 25 publications
0
40
0
1
Order By: Relevance
“…Intentional non-adherence sometimes results from denial about the seriousness of diabetes [ 47 , 57 , 65 , 68 , 77 , 90 ]. Denial of the severity of diabetes may relate to the belief that “everybody’s got it” [ 90 ], or to the underlying scepticism and lack of trust about the effectiveness of the treatment coupled with the fear that the prescribed medication is unnecessary, unhealthy, or dangerous [ 44 , 50 , 80 , 89 , 91 ]. Most commonly patients decide not to adhere to medication regimens as an effort to avoid side effects [ 50 , 67 , 68 , 78 , 79 , 89 , 92 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intentional non-adherence sometimes results from denial about the seriousness of diabetes [ 47 , 57 , 65 , 68 , 77 , 90 ]. Denial of the severity of diabetes may relate to the belief that “everybody’s got it” [ 90 ], or to the underlying scepticism and lack of trust about the effectiveness of the treatment coupled with the fear that the prescribed medication is unnecessary, unhealthy, or dangerous [ 44 , 50 , 80 , 89 , 91 ]. Most commonly patients decide not to adhere to medication regimens as an effort to avoid side effects [ 50 , 67 , 68 , 78 , 79 , 89 , 92 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding underscores the critical importance of oral communication strategies in interactions with patients with low health literacy for diabetes education. As shown in a recent qualitative study, even though diabetes educational materials are generally accompanied by easyto-follow instructions or are used with educational technology, many challenges for improving health behavior remain, such as language discordance and lack of consideration of health beliefs (Mohan, Riley, Boyington, & Kripalani, 2013). Spoken communication centered on patients accommodating low health literacy may improve patients' health through discussion about their illness experiences as well as agreements on treatment options regarding diabetes management (Stewart et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Recent research suggests that communication between patients and medical providers may be especially important in promoting engagement and treatment adherence among Latinos (Villagran et al, 2012), so it is essential that providers present health recommendations in a clear and culturally appropriate manner. Along these lines, Mohan et al (2013) suggested that illustrated diabetes management instructions may be useful with Latino patients as a supplement to traditional verbal or written directions, particularly for patients who speak limited English.…”
Section: Discussionmentioning
confidence: 99%